Risk and Savings: a Taxonomy - Jan Willem Gunning (Tinbergen Institute, 2008)
Risk may induce precautionary saving but it can also reduce saving. The theoretical literature recognizes both possibilities, but favors a positive effect (both for developed and developing countries); the empirical literature is divided, reporting (small) positive effects for developed economies and (large) negative effects for developing countries. We show in a 2-period model how the effect of risk on savings depends not only on preferences but also on the type of risk.
Keywords: D11; D91; O12; O16; 330; Theory Consumer Economics; Intertemporal Consumer Choice; Microeconomic Analyses of Economic Development; Economic Development; Financial Markets; Saving and Capital Investment; Corporate Finance and Governance; Sparen; Risikopräferenz; Konsumtheorie